Tingkat Difusi Oksigen Selama Periode Blind Feeding Budidaya Intensif Udang Vaname (Litopenaeus vannamei) - Ariadi, Heri; Wafi, Abdul; Supriatna, Supriatna; Musa, Muhammad (Rekayasa, 2021)
The diffusion process is a limiting factor that key plays for the oxygen transfer mechanism in the pond water column. The purpose of this study was to determine of oxygen diffusion rate during the blind feeding period of intensive shrimp culture of vaname (L. vannamei). This research was conducted for 30 days blind feeding period of intensive vaname shrimp culture, the research using concept of ex-pose facto causal design. Furthermore, the oxygen diffusion rate is calculated mathematically and a regression test is carried out on the associated water quality parameters. During the blind feeding period, the oxygen diffusion rate fluctuates and dynamically, with a diffusion rate ranging from 0.015-0.028 mgO2/L/hour. This condition is followed by a stabilizing and optimum condition of pond water quality parameter values throughout in the aquaculture. Diurnal periodically, the oxygen diffusion mechanism has an influence on the level of oxygen solubility in ponds. This relationship is modeled by the equation Y = 0.006 + 0.002x. This means that for each diffusion transfer increase of 1 mgO2/L/hour, there will be an oxygen increase in the ponds of 0.002 mg/L. The conclusion of this study is that the oxygen diffusion rate during the blind feeding period of intensive vaname shrimp culture obtained an average at 0.020 mgO2/L/hour, ranging from 0.018-0.023 mgO2/L/hour for 30 days of culture. From the results of this study, it is hoped that research can be developed study regarding of mechanisms, dynamics, and the effect of oxygen diffusion on the intensive shrimp farming ecology.